Ski economy and physiological responses while double poling - curved vs. straight poles - Mishica, C.; Ohtonen, O.; Leppävuori, A.; Linnamo, V. (Sciene and nordic skiing III, 2016)
Today, competitive cross country (XC) skiing is a very demanding sport. High maximal oxygen uptake, good skiing technique, fast force production, and a high ability to resist fatigue are all necessary to compete successfully. At the highest level, improvements are often subtle and require an optimal training program to see even the smallest performance gains. One technique that is commonly used in XC skiing is double poling (DP). It is a main technique and critical component in XC skiing and it is often an exclusive technique in competitions today. As a result, increased demands have been made on a skier's ability to reach high DP velocities and on the value of research focusing and finding possible performance gains by using this technique. DP is a complex movement that involves both the upper and lower body. During this technique, muscles are activated in sequential order starting with the trunk and hip flexors, followed by shoulder extensors and the elbow extensor triceps brachii (Holmberg et a!., 2005). Ski poles allow a skier to apply power and force to the snow and their composition and design have a significant effect on performance. Different pole lengths and cross sections are some of the differences that have been tested. Advancements in equipment will continue to be introduced so it is important to have research that supports the possible benefits and physiological reasoning behind these changes. Thus, the purpose of this study was to determine if curved ski poles showed improvements in double pole performance or reductions in blood lactate and heart rate values by comparing them to traditional straight ski poles. The second aim was to compare the gross efficiency values of the two pole types to see if any differences in ski economy were visible. The third aim was to investigate gender differences and see whether males and females have similar or different responses when performing submaximal tests. (Original introduction)